Evaluation of Leaf Spot and Blight Diseases in Mahogany (Swietenia mahagoni) Seedlings in Rumpin Nursery, Bogor Regency, Indonesia - Islami, Naluri Siyasah; Istikorini, Yunik; Lelana, Neo Endra; Wulandari, Arum Sekar (Pusat Penelitian Lingkungan Hidup, IPB (PPLH-IPB) dan Program Studi Pengelolaan Sumberdaya Alam dan Lingkungan, IPB (PS. PSL, SPs. IPB), 2026)
Seedling propagation in nurseries often faces problems such as disease attack. Leaf spot and blight are the main threats that usually hamper the growth of small-leaf mahogany (Swietenia mahagoni (L.) Jacq.) seedlings in the nursery. This study aims to determine the incidence and severity of disease, factors affecting the development of leaf spot and blight on small-leaf mahogany seedlings, and identify the causative pathogen. The research method included observations of disease incidence and severity in two sample plots representing the nursery with a sampling intensity of 10%. Leaf samples showing disease symptoms were isolated and tested for Koch’s Postulates. The result showed that the incidence of leaf spot and blight reached 95,44% and the disease severity was lower (44,72%). The environmental conditions at Rumpin Nursery, including high rainfall and humidity, as well as moderate temperatures (22-30 °C), favored the spread of disease. There were four types of fungal pathogens of leaf spot and blight on small-leaf mahogany seedlings, namely Pestalotiopsis sp., Rhizoctonia sp., Colletotrichum sp., and Bipolaris sp., with an incubation period of 1-2 days. This incubation period indicates rapid infectious ability under favorable environmental conditions.